Fenomenologi Popularitas Organik Pengguna Non-Selebriti di Instagram - Adhvidya Adhvidya (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This journal examines the process of forming popular accounts on Instagram, carried out by individuals from ordinary backgrounds rather than celebrities or public figures. The study employs a qualitative approach with a descriptive phenomenological method to gain an in-depth understanding of participants’ experiences. Three participants were selected through purposive sampling based on the criterion of owning accounts that had already gained wide recognition. The research aims to answer a fundamental question: what truly creates a popular account on Instagram? The analysis reveals that popularity does not necessarily stem from an explicit motive to become popular, but rather emerges as a consequence of consistent and authentic everyday practices. Four main strategies identified in this study are consistency in posting content, creating characteristic content, engaging in reposting practices, and meeting followers’ expectations. These findings contribute significantly to the field of digital communication studies and serve as practical references for Instagram users seeking to understand the dynamics of popularity without relying on instant strategies. Ultimately, the results not only provide empirical insights into how popular accounts are formed but also establish a conceptual foundation for next development of communication studies. In theoretical terms, this study expands the understanding of how digital identity, everyday practices, and social interactions intersect in shaping popularity within social media spaces.